Introduction, Analysis, and Critique for Ethics: A Pluralistic Approach to Moral Theory - Maryam Saneapour; Amir Sadeghi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article introduces, analyzes, and criticizes the work of Lawrence M. Hinman, Ethics: A Pluralistic Approach to Moral Theory. Hinman is a Philosopher of Ethics in the multimedia learning. He believes that multiculturalism is important factor of nowadays so the most important responsibility of philosophers of Ethics is prevention of moral conflict. The global communication and information in 21st  century needs global  tolerance and respect of various nations, cultures, and moralities together because different people and societies have a common  human nature and common natural rights that obligate to justice and moral relationship between  different people and  various societies’ beliefs throughout the world. Moral communication in multiculturalism approach is against racial, gender, national, and ethnic prejudice. Hinman believes in moral dialogue and global learning across different cultures. The book of Ethics: A Pluralistic Approach to Moral Theory has a proper category of new ethical problems, and the candid standpoint of author is considerable. He has a logical method, and in the end of every part of book there are some questions for evaluation of students learning. So this book is proper for the philosophy of ethics in universities.